Experimental in vitro modeling of hematopoiesis by using diffusion chambers of an original design - Denys Bilko (Annals of Bone Marrow Research - Peertechz Publications, 2022)
One of the most important tasks of biotechnology and regenerative medicine is to achieve long-term expansion of hematopoietic stem cells. One of the promising approaches to optimizing the cultures of hematopoietic cells is the creation of a microenvironment in the form of feeder stromal layers, which allows for the reproduction of the combination of soluble cytokines and growth factors necessary for hematopoiesis and promotes an increase in their proliferation [1,2].